Generation of lysolipin derivatives by genetic engineering - Robertsen, Helene; Rohrer, Sabrina; Kulik, Andreas; Wohlleben, Wolfgang; Mast, Yvonne (Frontiers in Chemical Biology, 2024)
Lysolipin I is a halogenated, polycyclic xanthone natural product belonging to the polyketide class of antibiotics, naturally produced by Streptomyces violaceoniger TÜ96 and Streptomyces tendae TÜ4042. The biosynthesis is encoded on a 43 kb-spanning biosynthetic gene cluster. Heterologous expression of the gene cluster has been established in previous work by using the cosmid 4H04, which was transferred to Streptomyces albus. In the current study, we demonstrate the optimization of production yields of therapeutically interesting lysolipin derivatives with extended activity against Gram-negatives and less cytotoxic bioactivities, respectively, by using mutated heterologous S. albus producer strains. Production yields were significantly increased by adapting cultivation conditions as well as by inactivating the transcriptional repressor gene llpRI, which lead to increased and consistent lysolipin (derivatives) production. Furthermore, cultivation of a S. albus 4H04∆llpOI mutant strain in bromide-containing fermentation medium resulted in the production of a new brominated lysolipin derivative (C28H20BrNO9).